Y-Stenting for Bifurcation Aneurysm Coil Embolization: What is the Risk? - Alejandro M. Spiotta; Jonathan Lena; M. Imran Chaudry; Raymond D. Turner; Aquilla S. Turk (Stroke Research and Treatment)
The use of two stents in a “Y” configuration (Y-stenting) to assist with coil embolization of complex bifurcation aneurysms has been accepted as an alternative to clip reconstruction of a select subset of challenging aneurysms. We review the risks associated with Y-stenting, including its procedural complication rates, angiographic occlusion rates, rerupture, and retreatment rates.